The effects of the breakup of AT & T on telephone penetration in the United States - Hausman, Jerry A.; Tardiff, Timothy J. (American Economic Review, 1993)
The breakup of ATT that is, the price of basic access was well below its incremental (or marginal) cost. The largest component of this cross subsidy arises from the prices of long-distance services, which are well in excess of their incremental cost. However, since the price elasticity of basic access is near zero while the price elasticity of long-distance services varies from about -0.25 to 1.2 depending on the type of service, a large economic efficiency loss occurs. Why did' regulation evolve in the United States to cause this extremely large distortion in prices? Numerous reasons can and have been put forward (see e.g., Peter Temin, 1987), but our favorite explanation arises from a combination of an outmoded framework of telecommunications regulation and changing technology. Congressional legislation, which established the Federal Communications Commission (FCC) and remains the basic framework for telecommunications regulation, was the Communications Act of 1934. This legislation led to the current joint regulation of telephone companies by both the FCC and state public utility commissions (PUC's). The Communications Act codified the goal of universal service-the notion that all U.S. households should have telephone service. This policy has been quite successful with U.S. telephone penetration at 93.3 percent in 1990 according to the Current Population Survey (CPS). Yet the FCC is basically in charge of setting long-distance prices while state PUC's are in charge of setting basic access prices, both of which are important factors in telephone penetration. During the post-World War II period the technology was changing so that the of long-distance service was decreasing markedly while the of labor-intensive basic access continued to rise essentially in line with inflation. The so-called separations system of regulation, established to divide the cost of the public telephone network between federal and state regulatory jurisdictions, created increasing cross subsidies as the contribution from long distance grew with increases in both the price-cost ratio of long distance and increases in long-distance demand. Economists were aware of this problem and in the 1970's recommended that longdistance prices be decreased and basic access prices be increased. Indeed, to a first approximation if the basic access price elasticity is zero, the first-best tax solution of a tDiscussants: Glenn A. Woroch, GTE Laboratories; Molly K. Macauley, Resources for the Future; Gerald Faulhaber, University of Pennsylvania.